2015
DOI: 10.1155/2015/525901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of Cognitive Training on Cognitive Function, Brain Structure, and Driving Safety in Senior Daily Drivers: A Pilot Study

Abstract: Background. Increasing proportion of the elderly in the driving population raises the importance of assuring their safety. We explored the effects of three different types of cognitive training on the cognitive function, brain structure, and driving safety of the elderly. Methods. Thirty-seven healthy elderly daily drivers were randomly assigned to one of three training groups: Group V trained in a vehicle with a newly developed onboard cognitive training program, Group P trained with a similar program but on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 87 publications
0
30
1
Order By: Relevance
“…We also noted that these regions did not overlap with the regions showing structural changes after cognitive intervention (Nozawa et al. ). The Fieldtrip software package (Oostenveld et al.…”
Section: Methodsmentioning
confidence: 53%
See 2 more Smart Citations
“…We also noted that these regions did not overlap with the regions showing structural changes after cognitive intervention (Nozawa et al. ). The Fieldtrip software package (Oostenveld et al.…”
Section: Methodsmentioning
confidence: 53%
“…Indeed, Group V but not Group P showed significant improvements in cognitive functions as assessed by the neuropsychological test battery (Nozawa et al. ). Previous studies have shown that not only cardiovascular (aerobic) exercise but also coordinative exercise could improve cognitive functioning in older adults (Voelcker‐Rehage et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we did not include measurements related to everyday behaviors such as driving. Previous studies demonstrated that cognitive training improves driving skills in elderly people (Edwards et al, 2009b; Nozawa et al, 2015). To generalize the effects of short-term processing speed training, it is necessary to verify the positive effects of the short-term processing speed training on everyday behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, children with a lower baseline may benefit more from training, whereas, in older adults, those with higher baseline education seem to perform better with training . Furthermore, in older adults, one specific everyday domain has received some attention: the development of specific training programs for improving car‐driving performance and safety, with rather consistent, successful results …”
Section: Nonpharmacological Interventions To Enhance Cognitive Performentioning
confidence: 99%